Christian Response to Reproductive Technologies: A Case Study of Artificial Insemination - Ekpenyong Nyong, Akpanika; Okon Ben, Anthony (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The scientific method of artificial insemination is one of the reproductive technology that came into widespread use some decades ago. With this method, some couples with fertility problems can now have children through artificial insemination; a process where concentrated male semen is introduced into the female reproductive system artificially in the clinic for childbearing. The increasing cases of childlessness, infertility or barrenness among married couples and request from the homosexuals (gay and lesbians) have given rise to high demand for artificial insemination. Today, there are commercial sperm banks that store frozen sperms for sell to those who need them. This artificial method of childbearing has generated serious controversy among theologians, bioethical and Christian scholars. Artificial insemination has indeed given hope to many couples globally whose marriages were threatened due to the problem of barrenness, childlessness or reproductive malfunctioning. The major Christian and ethical concern is that the process is artificial and manipulative rather than being natural. This paper aims to examine the biblical perspective of this phenomenal scientific breakthrough and show whether or not artificial insemination is compatible with the Christian doctrine of marriage and childbearing. The research method adopted is descriptive, using secondary materials from journals, textbooks and websites to elucidate the points. The study reveals that there is no consensuses agreement on the issue of reproductive technology among Christian scholars and the biblical interpretation of some related passages are not explicit on issues of reproductive technology. The study, therefore, recommends a more natural way of treating the issues of infertility, barrenness and childlessness by investigating into the causes of infertility and proffer a curative solution rather than resort into masturbation and commercialization of human sperm and egg.